Plumbagin inhibits growth of gliomas in vivo via suppression of FOXM1 expression - Mingshan Niu (Journal of Pharmacological Sciences, 2015)
Plumbagin is a natural compound that is isolated from the root of the medicinal plant Plumbago zeylanica L. Based on a previous in vitro study performed by our group, which demonstrated the effectiveness of plumbagin against glioma cells, we further ascertained whether plumbagin exhibits the same effectiveness against glioma cell xenografts in nude mice. Our results revealed that tumor volume was reduced by 54.48% in the plumbagin-treated group compared with the controls. Furthermore, there were no obvious signs of toxicity as assessed by the organ sizes and cell morphologies of the mice that were treated with plumbagin. Immunoﬂuorescence assays further revealed that plumbagin significantly inhibited glioma cell proliferation and induced cell apoptosis. Importantly, we also determined that the expressions of FOXM1 and its downstream target effectors, including cyclin D1 and Cdc25B, were down-regulated in the treated group, while the expressions of p21 and p27 were increased; the latter findings corroborate the results of our previous in vitro study. Taken together, these findings indicate that plumbagin may be a natural downregulator of FOXM1 with potential therapeutic effectiveness for the treatment of gliomas.